2020
DOI: 10.3389/fneur.2020.00492
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Tirofiban in Rescue Treatment for Acute Intracranial Intraprocedural Stent Thrombosis

Abstract: Background and Purpose: The incidence of acute intraprocedural stent thrombosis (AIST) during stenting of intracranial atherosclerotic stenosis (ICAS) has seldom been reported and evidence regarding the treatment of AIST is lacking. We aim to investigate the incidence of AIST during stenting of ICAS in our institute, assess the preliminary efficacy and safety of rescue treatment of tirofiban for these patients. Methods: From September 2016 to May 2019, all symptomatic ICAS patients who underwent intracranial s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Several retrospective studies and case series have demonstrated a favourable effect of the systemic administration of tirofiban on patients with intracranial dissection [30] and on patients after emergency angioplasty with and without intracranial stenting [31,32]. The main advantages of the drug are its ease of administration, rapid onset of action and short half-life.…”
Section: Discussionmentioning
confidence: 99%
“…Several retrospective studies and case series have demonstrated a favourable effect of the systemic administration of tirofiban on patients with intracranial dissection [30] and on patients after emergency angioplasty with and without intracranial stenting [31,32]. The main advantages of the drug are its ease of administration, rapid onset of action and short half-life.…”
Section: Discussionmentioning
confidence: 99%
“…According to a single-centre observational study by Zhao W et al, intra-arterial “low-dose” tirofiban was used to cope with thromboembolic complications and the authors advised using a 0.25–0.5 mg (total) dose at a rate of 1 ml/min (0.05 mg/ml) or 0.4 µg/kg/min for 1000 s (up to 1 mg in total). 25 , 38 This was not associated with an increased incidence of symptomatic intracranial hemorrhage. In summary, both intravenous and intra-arterial approaches have been described with similar clinical outcomes and complication rates.…”
Section: Tirofibanmentioning
confidence: 85%
“…24 Moreover, during acute intraprocedural stent thrombosis in the context of intracranial atherosclerotic stenosis, intra-arterial bolus administration of tirofiban followed by IV infusion was efficacious and safe with no significant increased risk of intracranial hemorrhage or death. 25 With regards to mechanical thrombectomy, intra-arterial administration of tirofiban was beneficial predominantly for large artery atherosclerosis strokes relative to those of cardio-embolic origin. 26 Conversely, a randomized control trial found no significant effect of tirofiban in AIS on long-term survival, dependency or death without increasing the risk of bleeding compared to using aspirin.…”
Section: Tirofibanmentioning
confidence: 99%
“…All patients were on dual antiplatelet agents (100 mg aspirin and 75 mg clopidogrel) daily for at least 5 days before stenting. The details of the interventional procedure have been described previously 8 , 9 . In brief, all endovascular procedures were performed by an experienced neurointerventionist under general anesthesia between 1 and 3 weeks after the symptoms onset of the last ischemic stroke.…”
Section: Methodsmentioning
confidence: 99%
“…When the stent was released, the intraoperative angiography showed a shadow defect within 5 mm to the stent or within the stent, AIST was recorded. For patients diagnosed with AIST, intra-arterial bolus followed by intravenous tirofiban infusion as a rescue therapy without other methods such as additional angioplasty or stenting was adopted as described in our previous study 8 and remedial recanalization was evaluated by modified Thrombolysis In Cerebral Infarction (mTICI) scale and Arterial Occlusive Lesion (AOL) scale 10 .…”
Section: Methodsmentioning
confidence: 99%